Low-intensity focused ultrasound of the spine in the treatment of chronic pain and movement disorder: a scoping review - Seol, Kyung; Hong, Brian; Kelhofer, Nicolas; Pappu, Suguna; Oelze, Michael (Frontiers in Pain Research, 2025)
Low-Intensity Focused Ultrasound Stimulation (LIFU) is a noninvasive and nondestructive neuromodulatory method with growing evidence for the safe and effective treatment of chronic pain. However, the effect of LIFU applied to the spine region, including the spinal cord and dorsal root ganglia, is not well understood. In this work, we review current advances in LIFU of the spine region for the treatment of chronic neuropathic pain and movement disorders to explore potential clinical applications and indicate a direction for future study. To assess the current state of LIFU application to pain modulation over the spinal cord region, a systematic search was performed according to PRISMA guidelines using PubMed, Web of Science, Scopus, and citation matching through December 17, 2024. Inclusion criteria were English language, non-tissue-damaging ultrasound neuromodulation, intervention over the spinal cord region, and relation to neuropathic pain. Exclusion criteria were existing review papers, extracorporeal shockwave therapy, tissue-destructive ultrasound treatments, non-focused ultrasound, and in vitro experiments. Preliminarily, title and abstract screening identified 15 studies, all using animal models. While results varied with different target sites and ultrasound parameters, LIFU was found to reduce allodynic response and suppress movement disorders such as spasticity and tremor. There are limited animal studies and no completed human clinical trials that analyze the effect of LIFU on spinal neural tissue. Further, there has not been a study that aims to optimize ultrasound parameters in the spine region or a thorough investigation correlating targets in the spinal regions to the desired outcome. We reviewed the current understanding of LIFU of the spine region for treating chronic pain, spasticity, and tremors to identify current advances and gaps in the literature. Our review highlights the need for further study in the efficacy and safety of LIFU applied to the spinal region of animals and humans, given the wide variation in sonication parameters, inconsistent treatment effects, and unexplored mechanisms of action.